Installation of Soil Pressure Cells in Civil Engineering Structures - Grabowski, L.; Kobielak, S.; Zamiar, Z.; Jagiello, M. (Communications - Scientific letters of the University of Zilina, 2002)
The paper deals with the problem of cells installation encountered with the measuring of soil pressure in different civil engineering structures. In the paper are given application examples of boundary type of pressure cells used to pressure soil measurement acting on boundary surfaces of such civil engineering structures as building foundation, tunnels, shafts, piles and retaining walls as well as embedded type pressure cells apllied to stress record within soil of road or dam embankments. When pressure cells are installed for such measurements suitable installation techniques should be used to minimise ground disturbance in the vicinity of the pressure cells which affects considerably their indications. In the work different techniques of the cells installation have been presented.